2021
DOI: 10.1159/000513664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intensive Weight-Loss Lifestyle Intervention on Kidney Function: A Randomized Controlled Trial

Abstract: <b><i>Introduction:</i></b> Large randomized trials testing the effect of a multifactorial weight-loss lifestyle intervention including Mediterranean diet (MedDiet) on renal function are lacking. Here, we evaluated the 1-year efficacy of an intensive weight-loss intervention with an energy-reduced MedDiet (erMedDiet) plus increased physical activity (PA) on renal function. <b><i>Methods:</i></b> Randomized controlled “PREvención con DIeta MEDiterránea-Plus” (PRED… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Indeed, other injury pathways have been implicated, notably a role of increased inflammation with adipokine dysregulation, neurohumoral activation, and increased sodium reabsorption [31]. Similar to our study, a recent RCT trial assessing the effect of a weight-loss lifestyle intervention based on an energy-restricted Mediterranean diet showed favorable one-year outcomes by reducing eGFR decline [32]. However, the mean achieved weight loss was only 3.7 kg, which seems lower than the 8% objective of weight reduction of the study and much lower than the magnitude of weight reduction obtained in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, other injury pathways have been implicated, notably a role of increased inflammation with adipokine dysregulation, neurohumoral activation, and increased sodium reabsorption [31]. Similar to our study, a recent RCT trial assessing the effect of a weight-loss lifestyle intervention based on an energy-restricted Mediterranean diet showed favorable one-year outcomes by reducing eGFR decline [32]. However, the mean achieved weight loss was only 3.7 kg, which seems lower than the 8% objective of weight reduction of the study and much lower than the magnitude of weight reduction obtained in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The best option to estimate GFR in patients who are obese remains an unsolved issue, with specific questions, such as the indexation to body surface area, and even cystatine-C appears to be influenced by body fat [41]. Hence, as an example, in the study by Diaz-Lopez et al [32], the mean eGFR difference between both groups was very low; meanwhile, no difference in mean urine albumin-to-creatinine ratio was noted, which could testify that the mean eGFR difference did not represent a significant clinical effect of the intervention. Thus far, there is no validated equation for the estimation of the renal function of patients who are obese, and the MDRD equation can be biased in this population [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent weight-loss intervention-based study, PREDIMED-Plus, the 1-year consumption of an energy-reduced Mediterranean diet and increased physical activity (intervention group) led to a lower decline in eGFR, in comparison with the control group, who were given the usual advice recommending a Mediterranean diet, in overweight/obese adults with metabolic syndrome [13]. In this study, the eGFR decline rate was z0.6 mL/min/1.73 m 2 lower in the intervention group than in the control group, which could be partly attributed, according to the authors, to weight loss in the patients following this diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we confirmed that MetS was a significant risk Health Educ Public Health 2022, 5:2 factor for mortality [18]. Therefore, early intervention in overweight/obese adults, namely MetS subjects is necessary to prevent the progression of CKD [24,25] and death.…”
Section: Discussionmentioning
confidence: 95%